Calculation of the bending radius of stripe at squeezing in rolls - L. A. Isajevich; S. V. Ivanitskij (Литьë и металлургия)
There is shown, that at rolling with discrepancy of the surface speeds of bowls, at changing of rate of squeezing and discrepancy of the surface speeds of bowls it is possible to gain the bending of bar to rib for necessary radius along the whole length of the bar.